Erasmus syndrome presented as CREST syndrome with Scl-70 positivity: a case report - Pereira, Felipe; Miranda Portilho , João Vitor; Viana de Rezende Meira , João Paulo; Ribeiro de Paula, Carmen Dea (Brazilian Journal of Case Reports, 2021)
Erasmus syndrome is a rare pathology defined as a systemic sclerosis secondary to contact with silica, associated or not with silicosis. More recent studies have related silica as an environmental factor stimulating different immune responses of the body. This report was made with the objective of presenting a rare case of systemic sclerosis, in a localized cutaneous form, also called CREST syndrome. A patient with a 20-year history of mining developed silicosis, cutaneous calcinosis, Raynauld’s phenomenon, esophagopathy, sclerodactyly, telangiectasias and high positivity for the antitopoisomerase I antibody, the most common antibody in the systemic form.